2005
DOI: 10.1088/0031-9155/50/4/011
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of synchrotron radiation intravenous angiographic images

Abstract: A medical research protocol on clinical intravenous coronary angiography has been completed at the European Synchrotron Radiation Facility (ESRF) biomedical beamline. The aim was to investigate the accuracy of intravenous coronary angiography based on the K-edge digital subtraction technique for the detection of in-stent restenosis. For each patient, diagnosis has been performed on the synchrotron radiation images and monitored with the conventional selective coronary angiography method taken as the golden sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The results of these in vitro studies proved to be so encouraging that a clinical program that involved performing mammographic examinations with x-rays from Elettra, the synchrotron radiation facility in Trieste, Italy, was launched as part of the Synchrotron Radiation for Medical Physics (SYRMEP) Project ( 19 ). The x-rays generated from synchrotrons were used in digital coronary angiography examinations conducted in 470 patients between 1979 and 2000 (20)(21)(22)(23)(24)(25). To our knowledge, however, investigators in no previous studies have analyzed the diagnostic capabilities of T he standard method for diagnosing breast cancer at an early preclinical stage is screen-fi lm mammography or digital mammography (DM), even though these are not perfect imaging tools.…”
Section: Patient Study Protocol and Reference Standardsmentioning
confidence: 99%
“…The results of these in vitro studies proved to be so encouraging that a clinical program that involved performing mammographic examinations with x-rays from Elettra, the synchrotron radiation facility in Trieste, Italy, was launched as part of the Synchrotron Radiation for Medical Physics (SYRMEP) Project ( 19 ). The x-rays generated from synchrotrons were used in digital coronary angiography examinations conducted in 470 patients between 1979 and 2000 (20)(21)(22)(23)(24)(25). To our knowledge, however, investigators in no previous studies have analyzed the diagnostic capabilities of T he standard method for diagnosing breast cancer at an early preclinical stage is screen-fi lm mammography or digital mammography (DM), even though these are not perfect imaging tools.…”
Section: Patient Study Protocol and Reference Standardsmentioning
confidence: 99%
“…However, it should be considered that conventional digital subtracted angiography and K-edge subtraction angiography are also performed by acquiring two images. Concerning the latter technique, Sarnelli et al 14 reported dose values below the law limit. Segmentation alone may be not sufficient to distinguish small vessel in a noisy background.…”
Section: Discussionmentioning
confidence: 99%
“…12 An angiographic technique more effective than the conventional DSA has been implemented at the medical beamlines of some synchrotrons. [13][14][15][16][17] This technique, called K-edge subtraction angiography, consists in the acquisition of two images, one produced by a monochromatic beam having energy just above the K-edge of the contrast medium, the other produced by a beam having energy just below the K-edge. Also in this case, the difference between the two images yields the distribution of the contrast medium, while the other structures are removed.…”
mentioning
confidence: 99%
“…Using the dualenergy KES-CT imaging method, the absolute density due to tissue or to the contrast agent can be calculated separately. The two acquired images are subtracted before the reconstruction, and tissue and Xe density images are reconstructed separately using a computer algorithm explained in detail elsewhere (Sarnelli et al, 2005). The concentration of the contrast agent can be measured within each voxel or region of interest from the Xe density images.…”
Section: K-edge Subtraction Imagingmentioning
confidence: 99%